Do previous experience and geographic proximity matter? Possible predictors for diagnosing Adjustment disorder vs. PTSD. (December 2017) - Mahat-Shamir, Michal; Ring, Lia; Hamama-Raz, Yaira; Ben-Ezra, Menachem; Pitcho-Prelorentzos, Shani; David, Udi Y.; Zaken, Adi; Lavenda, Osnat
Abstract: The minority of people who have experienced a traumatic event and were diagnosed as either suffering from PTSD or from Adjustment disorder, may suggest that victims of a traumatic event vary in risk factors for the disorders. The current research aimed at examining the association between reports of Adjustment disorder and PTSD symptoms (In accordance with the proposed revisions of the ICD-11) and several vulnerability variables: previous traumatic event, previous stressful event and physical proximity to the terror attack. Using an online survey, 379 adult participants were recruited, and filled out Adjustment disorder, PTSD symptomatology scales, as well as a previous exposure, magnitude of exposure and death anxiety scales. Findings revealed that previous experience of traumatic events was a significant predictor associated with both PTSD and Adjustment disorder symptoms. Previous experience of stressful events was a significant predictor associated with Adjustment disorder alone. Physical proximity to the site of the attack was a significant predictor associated with PTSD symptoms but not Adjustment disorder symptoms. The importance of previous traumatic events, previous stressful events and physical proximity to the terror attack as factors which are associated with Adjustment disorder and PTSD symptomatology is discussed. Highlights: Differentiation between adjustment disorder and PTSD is understudied. Suggested key variables were previous exposure and magnitude. Magnitude and previous exposure to traumatic event were associated with PTSD. Previous exposure to stressful and traumatic events were associated with adjustment disorder. ICD-11 stress spectrum is being supported by the study.